Cross-Docking Operations for Supply Chain Logistics in JIT Production and Distribution Systems - Thapa, Gyan Bahadur; Dhamala, Tanka Nath; Pant, Shankar Raj (Journal of the Institute of Engineering, 2011)
The multi-level production problem is one of the challenging research areas in supply chain management. We present brief literature review and mathematical models of multi-level just-in-time sequencing problem with a view of cross-docking approach for supply chain logistics. Describing cross-docking operations, we propose a mathematical model for the cross-docking supply chain logistics problem to minimize the operation time as truck sequencing problem. We establish a proposition as the synthesis of the production and logistics. Key Words: Just-in-time; Supply chain; Logistics; Cross-dock; Operation time DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5114 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 219-230 Uploaded Date: 20 July, 2011